Digital Governance for Confiscating Crypto-Assets to Settle Tax Liabilities in Indonesia - Aruan, Albert Richi; Toha, Kurnia; Nurdin, Aad Rusyad (Aptisi Transactions On Technopreneurship (ATT), 2025)
The emergence of digital and virtual assets has created new challenges for tax authorities, as taxpayers now possess not only traditional but also digital assets that can be accessed globally through the internet. This unconventional form of asset ownership raises questions about how tax authorities can effectively confiscate and liquidate crypto-assets to resolve tax liabilities. The lack of these mechanisms complicates tax administration and criminal law enforcement in the digital era. This study aims to examine the possibility of confiscating digital and virtual assets for tax purposes within Indonesia’s asset recovery framework. Using a comparative law approach, this article analyzes the potential use of crypto-asset confiscation for the settlement of tax arrears by referencing the latest European Union regulations on asset recovery and confiscation, particularly the Directive (EU) 2024/1260 of the European Parliament and Council on asset recovery and confiscation. The analysis shows that Indonesia currently lacks a system that enables the confiscation and recovery of digital assets for tax enforcement. Considering the shared civil law foundations and similar challenges faced by EU countries, the EU’s model provides a relevant reference point. Indonesia should consider adopting the European Union’s methodology for seizing and recovering digital assets to enhance its legal framework. Implementing the asset recovery and confiscation mechanisms established under Directive (EU) 2024/1260 could serve as a paradigm for Indonesia to efficiently confiscate taxpayers’ assets and strengthen tax compliance in the digital economy.